'Roots in the soil': the evolution of a countryside youth service in Westmorland, 1939–c.1950. Issue 5 (3rd September 2022) - Andrew, Rebecca
ABSTRACT: This article traces the evolution of the statutory Youth Service in rural Westmorland (now part of Cumbria), from its establishment in 1939 to the early post-war years. It focuses on how the county's Youth Service innovated and developed new ways of working with young country people in their spare time, and the challenges of introducing urban-focused policy into rural practice. It argues that to be effective in work outside urban areas, the national Youth Service had to adapt to existing patterns of country life and leisure. Tensions between this external organising body and local communities are also considered. The article draws on official Youth Service records, including minute books, correspondence and annual reports, alongside local press accounts and oral history testimony. In doing so, it enhances our understanding of the professionalisation of informal education, and the leisure habits of rural youth, during and immediately after the Second World War.